How Second Language Learners from Mars and Venus Are Different in Lexical Acquisition - Windiana Argina, Ade; yakub, Sudirman; Oktafiani, Susi; Sobali, Utep (ASIAN PUBLISHER, 2023)
Up to the present day the issue of gender and language has been widely studied by numerous researchers not only by linguistics but also practitioners from other fields of study. The amount of research has been done through different methods, instrument and scope. These various approaches have brought contradictory answers of the questions - is there any effect of gender on the language acquisition? If so, to what extent gender demonstrates its influence on language learning? More specifically, does gender difference demonstrate different lexical acquisition of second language learners? Does gender solely affect second language learners lexical acquisition? Burning questions come up along with the various perspectives and paradigm held by practitioners. The complexity brings the impossibility to cover all of questions in one study. Therefore, this study is intended to contribute to sum up studies done in the field of how gender difference demonstrate its effects on second language learners lexical acquisition. By thematical approach, this library research presents a few studies related to gender lexical acquisition that have been available over the last twenty years. The contradictory findings are revealed, that is differences do exist with huge varieties in terms of lexical acquisition, vocabulary, learning strategy and lexical use. Yet, complex measurement of gender effect on lexical acquisition occurs as the effect of the potential existence of other variable factors. Some researchers believe that gender does not solely influence second language learners acquisition. They assume that various findings might be affected by some other variable factors that make male become male and make female become female or make language learners lost their gender identity or home whether they are from Mars or Venus in language acquisition. These variable factors include age, biological, social (context, experience & socialization), psychological, pedagogical (teaching & learning instruction) and linguistical (L1 & L2 relation)